Rehabilitation & Sports Medicine - Hanke L; Wedde L; Geisler S; Diel P; Isenmann E; 2 (Dynamic Media Sales Verlag, 2022)
Problems: Hypothyroidism is associated with increased cardiovascular events and a reduced quality of life. The goal of this systematic review is to identify additive treatment strategies besides hormone replacement through diet and exercise intervention and to point out research gaps. Methods: A comprehensive literature search was conducted in four databases (PubMed, Scopus, Science direct and SportDiscus) using defined MeSH words by two independent researchers. Literature from year 1990 onwards was considered. Results: To investigate the effects of diet and exercise on thyroid function, three randomized controlled trials and one comparative study with a total of 356 subjects (nutrition) and four randomized controlled trials with a total of 189 subjects (exercise) are identified. The nutrition-related studies show that nutritional interventions can reduce perceived symptoms in subclinical hypothyroidism. An effect on thyroid hormone serum levels has been demonstrated by an intake of selenium and phytoestrogens. Exercise-related studies show improvement in quality of life and symptoms through exercise in subclinical hypothyroidism. Changes in thyroid hormone serum levels could not be shown. Discussion: Due to the heterogeneous parameters recorded in the included studies, no clear conclusion can be drawn. Nevertheless, first findings show that nutrition and exercise have an effect on the symptoms of hypothyroidism. Both measures can reduce the development of comorbidities in subclinical hypothyroidism and improve quality of life. Studies combining both dietary intervention and exercise have not yet been conducted.Key Words: Endocrine disorders, Thyroid Hormones, Diet, Physical Activity, Quality of Life